The value of caudate lobectomy in hilar cholangiocarcinoma treatment: A meta-analysis. Issue 7 (19th February 2021) - Yang, Ming; Li, Wei Wei; Chen, Jian Hua; Cui, Miao Hang; Liu, Jin Long
Abstract: Purpose: To discuss the value of caudate lobectomy in hilar cholangiocarcinoma (HCCA) treatment. Methods: A systematic review was performed in PubMed, MEDLINE database, EMBASE, and Cochrane Library for trials comparing combined caudate lobectomy with controls from January 1, 1990 to December 2, 2020. The outcomes were postoperative radical cure information, survival condition, morbidity, and mortality. Result: Ten studies were included. No difference was observed in the morbidity (odd ratio (OR) 0.93, 95% confidence interval (CI) 0.65–1.33) and mortality (OR 1.16, 95% CI 0.55–2.42) between the combined caudate lobectomy and control groups. Hepatectomy combined with caudate lobectomy was associated with higher incidence of radical resection (OR 3.88, 95% CI 2.18–6.90) and longer survival (hazard ratio 0.45, 95% CI 0.38–0.55). Conclusion: Combining caudate lobectomy can significantly increase the incidence of radical resection of HCCA and the postoperative survival time. The morbidity and mortality were not increased after the operation. Thus, caudate lobectomy should be included when performing partial hepatectomy for HCCA.